2009
DOI: 10.1038/mt.2008.237
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-resident Macrophages Protect the Liver From Ischemia Reperfusion Injury via a Heme Oxygenase-1-Dependent Mechanism

Abstract: Kupffer cells are the resident macrophage population of the liver and have previously been implicated in the pathogenesis of hepatic ischemia-reperfusion injury (IRI). Kupffer cells are the major site of expression of hepatic heme oxygenase-1 (HO-1), which has been shown to have anti-inflammatory actions and to protect animals and cells from oxidative injury. Kupffer cells and circulating monocytes were selectively ablated using liposomal clodronate (LC) in the CD11b DTR mouse before induction of hepatic ische… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
104
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(110 citation statements)
references
References 37 publications
5
104
1
Order By: Relevance
“…It is not clear why CoPPIX did not result in HO-1 induction in hair cells or supporting cells in mouse utricles in vitro. The localization of HO-1 expression in macrophages observed herein is consistent with reports that HO-1 is expressed in macrophages of other organs, including liver and lung (Devey et al 2009;Obata et al 2011). Depletion of 75 % of the macrophages from utricular explants using LC abolished the protective effect of HO-1 induction (Fig.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It is not clear why CoPPIX did not result in HO-1 induction in hair cells or supporting cells in mouse utricles in vitro. The localization of HO-1 expression in macrophages observed herein is consistent with reports that HO-1 is expressed in macrophages of other organs, including liver and lung (Devey et al 2009;Obata et al 2011). Depletion of 75 % of the macrophages from utricular explants using LC abolished the protective effect of HO-1 induction (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, protection conferred from the HO-1/macrophage axis has been demonstrated in other systems, particularly in response to ischemiareperfusion injury in the liver (Devey et al 2009). In that system, HO-1 appears to regulate the cytokine secretion profile of the macrophages in a manner in which increased HO-1 expression results in a switch from pro-to anti-inflammatory cytokine secretion (Weis et al 2009;Wegiel et al 2013).…”
Section: Discussionmentioning
confidence: 97%
“…In liver cell injury, induced HO-1 preconditioning may lead to adaptive stress reaction, and may occur in response to organ ischemic insults, protecting the cells from injury (29,30). It has been suggested that ZnPP regulates heme catabolism through the inhibition of HO-1, and thus aggravates organ damage and cell apoptosis (31).…”
Section: Discussionmentioning
confidence: 99%
“…HO-1 is a stress-inducible protein highly expressed in Kupffer cells that displays potent protective anti-inflammatory and cytoprotective effects in the liver against alcohol-induced liver injury, 31 endotoxemia, 32 or ischemia-reperfusion injury. 33 We, therefore, investigated whether HO-1 might mediate CB2-induced anti-inflammatory effects in alcohol-fed mice and, first, characterized the impact of JWH-133 treatment on Kupffer-cell HO-1 protein expression by double immunohistochemistry combining antibodies to HO-1 and F4/80. Alcohol-fed mice treated with JWH-133 displayed a strong HO-1 protein increase in Kupffer cells, compared to alcohol-fed control animals (82% 6 2% versus 57% 6 3%, P < 0.05; Fig.…”
Section: Cb2mentioning
confidence: 99%